Proceedings of the 15th ACM Asia Conference on Computer and Communications Security 2020
DOI: 10.1145/3320269.3384744
|View full text |Cite
|
Sign up to set email alerts
|

XSS Vulnerabilities in Cloud-Application Add-Ons

Abstract: Many cloud-application vendors open their APIs for third-party developers to easily extend the functionality of their applications. The features implemented with these APIs are called add-ons (also called add-ins or apps). This is a relatively new phenomenon, and its effects on the application security have not been widely studied. It seems likely that some of the add-ons have lower code quality than the core applications themselves and, thus, may bring in security vulnerabilities. In this work, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Security-attack-based protections: Researchers have adapted several strategies to protect against several attacks, especially in a cloud-based system. Concerning cross-site scripting (XSS), Bui et al [ 17 ] found vulnerabilities in the APIs of cloud-based applications where external extensions might result in security flaws. For example, adversaries could exploit cloud services’ document sharing and messaging aspects to deliver malicious input.…”
Section: Resultsmentioning
confidence: 99%
“…Security-attack-based protections: Researchers have adapted several strategies to protect against several attacks, especially in a cloud-based system. Concerning cross-site scripting (XSS), Bui et al [ 17 ] found vulnerabilities in the APIs of cloud-based applications where external extensions might result in security flaws. For example, adversaries could exploit cloud services’ document sharing and messaging aspects to deliver malicious input.…”
Section: Resultsmentioning
confidence: 99%
“…Challenges related to improper access control: In their discussion of cloud add-ons, Bui et al [ 25 ] discussed instances where attackers may deliver malicious data to cloud services using their document-sharing and messaging capabilities. They mentioned to prevent add-ons from having unrestricted access to user information in the host application, cloud application suppliers often incorporate permission-based access control.…”
Section: Resultsmentioning
confidence: 99%
“…A common adopted classification is the one reported by OWASP itself that considers the location where untrusted data are supplied and processed: client-side and server-side XSS. This classification is adopted by several included studies [79,111,121,128,142,153]. In this review, we propose a more comprehensive classification based on the source of the vulnerability causing the attacks.…”
Section: Results Of the Search And Selection Processesmentioning
confidence: 99%